Improving Nurse Students’ Spoken English Skill through Problem-Based Learning - Ayendi Ayendi (Proceedings of ISELT FBS Universitas Negeri Padang, 2014)
The purposes of this research were to explain to what extent of PBL could improve nurse students’ spoken English skill, and to find out factors involved in the improvement. The participants of this research were nurse students of 2006 registered year of Nursing Program of Medicine Faculty at Andalas University. The methodology of this research was Classroom Action Research consisting of three cycles. Each cycle involved planning, acting, observing, and reflecting. Based on the research finding, after giving speaking task and speaking test during the first cycle, their spoken English skill was still fair. Therefore, the writer needed to continue the research to the second cycle. From the speaking test at the second cycle, it could be known that their spoken English skill was good, while from the speaking task, their spoken English skill has not good yet, so that the writer continued the research to the third cycle. During this third cycle, it seemed that their spoken English skill for the speaking task and the speaking test was better. In this case they have had correct accent, less mistakes in grammar, appropriate word choices, fluent speaking, and better understanding to the discussed topics. The factors known to be involved to the improvement were hidden spoken English skills, scenarios’ understanding, the availability of references, preparation, remembering ability, braveness, class atmosphere, and motivation.